ICT Transforming Teaching & Learning System - Prabha Raghuwanshi2, Vibha Thakur1, (International Journal of Scientific Research and Management (IJSRM), 2016)
ICT is a wide-ranging term which consists of all communication devices and applications, comprising: televisions, radios, computers, cellular phones and satellite systems, network hardware and software and etc., as well as the various applications and services allied with them, such as the Internet, broadcasting technologies, E-Learning systems, videoconferencing, virtual classes, E-meetings, E-collaborations and distance learning. During the past few years, the India has witnessed a phenomenal growth in communication technology, computer network and information technology. Improvement of new broadband communication services and convergence of telecommunication with computers have created numerous possibilities to use a variety of new technologies and tools for teaching and learning system. The integration of computers and communications offers unprecedented opportunities to the Higher Education Systems with its capacity to integrate enhance and interact with each other over a wide geographic distance in a meaningful way to achieve the learning objectives. ICT can be used as acre or a complementary means to the teacher training process.